Personal Computers in Clinical Research - McAlister, Neil (1984)
Personal computers have proved useful in several identifiable areas of clinical research support. However, they have limitations. Popular microcomputer systems typically fail to meet all of the traditional data processing requirements of serious clinical investigators — usually because of software restrictions. Objective evaluation of the strengths and weaknesses of these small systems, and particularly of their software, ensures effective use of research budgets and personnel. An analysis of clinical research needs that personal computers serve well, and of those that they serve poorly, is therefore presented.